Disiplin Kerja, Kompetensi, Pelatihan Kerja Pengaruhnya Terhadap Produktivitas Kerja Guru Tetap SMP Plus Cordova Banyuwangi - Vindha Ayu Novitasari; Hadi Sunaryo; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to describe work discipline, competence, job training, work productivity and analyze the effect of work discipline, competence, job training on the work productivity of permanent teachers at SMP Plus Corodova Banyuwangi. This study used a saturated sample, namely the permanent teachers of SMP Plus Cordova Banyuwangi, amounting to 36 people. Data collection techniques using a questionnaire with a likert scale. The work discipline variable is measured by using six indicators, competency four indicators, job training five indicators, and work productivity five indicators. The results of this study indicate that simultaneously work discipline, competence, job training have a positive and significant effect on work productivity. The results of this study also show that the work discipline variable has a positive and significant effect on teacher work productivity. The competence variable has a positive and significant effect on teacher work productivity. Job training variable has no effect on teacher work productivity. Keywords: work discipline, competence, job training, and teacher work productivity